Improving The Antioxidant Activity of Sodium Alginate from Sargassum sp. by Thermal Heating and Chemical Methods - Mila Safitri Rizfa; Ervia Yudiati; Diah Permata Wijayanti (Universitas Diponegoro, 2020)
The relationship between molecular structure and bioactivity was evaluated for sodium alginates obtained under different degradation treatment (raw alginates, heat-treated, and chemical-treated) from Sargassum sp. This study was conducted to identify the antioxidant activities of the degraded sodium alginate from Sargassum sp. compared to raw extract. Raw alginate as the control treatment was dried overnight at 60 °C, while heat-treated was heated raw alginate at 140oC in a laboratory oven (4.5 hours). Two chemical-treated were applied. Raw alginate added hydrogen peroxide and raw alginat with hydrogen peroxide plus ascorbic acid. This treatments were replicated three times. All the parameters were evaluated spectrophotometrically. The spectroscopy results from the degradation methods showed a new absorbance spectra pattern. The FT-IR spectrum revealed that treatment affects the structure of the alginates. Heat treated and chemical treated sodium alginates showed non significantly different on DPPH radical scavenging activity. Meanwhile, the combination of alginate and hydrogen peroxide treatment was at the lowest scavenging ability. Therefore, alginate oligosaccharides (AOS) produced by heating or adding chemical reagents could be considered as a stronger antioxidant than raw alginate, which may be applied in the industry and biomedical